Plasticizer, composition and tire
A temperature-responsive plasticizer with a specific interaction group addresses the lack of tire performance improvements in critical temperature ranges, enhancing tire performance through hydrophilicity and hydrophobicity changes.
Patent Information
- Application Number
- JP2020187834
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-11
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-11-11
AI Technical Summary
The tire industry has not focused on improving tire performance in the temperature range necessary for tires, and conventional technologies have not effectively addressed this need.
A plasticizer for resins and/or elastomers with a group that interacts with antifreeze and changes with temperature, having a lower critical solution temperature between -20°C to 20°C, is used to create a composition that can alter tire performance across a relevant temperature range.
The plasticizer enables tire performance changes in the required temperature range, enhancing fuel efficiency and wet grip performance by altering hydrophilicity and hydrophobicity in response to temperature variations.
Smart Images

Figure 0007615626000001 
Figure 0007615626000002 
Figure 0007615626000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a plasticizer, a composition and a tire. [Background technology]
[0002] 2. Description of the Related Art Various performance characteristics have been demanded of tires (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2008-214377 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, the tire industry has not paid much attention to changing tire performance in the temperature range required for tires, and conventional technology has room for improvement in terms of changing tire performance in the temperature range required for tires. The present invention has an object to solve the above-mentioned problems and to provide a plasticizer, a composition, and a tire that can change tire performance in a temperature range required for tires and can produce a tire composition. [Means for solving the problem]
[0005] The present invention relates to a plasticizer for resins and / or elastomers, which has a group whose interaction with an antifreeze solution changes depending on the temperature, and which has a lower critical solution temperature of -20°C to 20°C.
[0006] The plasticizer is preferably any one of an oil, an ester-based plasticizer, and a liquid or solid resin.
[0007] The above group is preferably a group represented by the following formula (I) or a group represented by the following formula (II). [ka] (In the formula, n represents an integer of 1 to 1000, R 1 , R 2 and R 3 each independently represents a hydrogen atom or a hydrocarbyl group. [ka] (In the formula, n represents an integer of 1 to 1000, R 4 represents an n-butyl group or a tert-butyl group, R 5 represents a hydrogen atom or a hydrocarbyl group.
[0008] The above groups are preferably poly(ethyl vinyl ether), poly(N-tert-butylacrylamide), poly(Nn-butylacrylamide).
[0009] The present invention also relates to a composition comprising the above plasticizer.
[0010] The composition preferably comprises a rubber.
[0011] The composition preferably contains, as the rubber, a multicomponent copolymer containing conjugated diene units, non-conjugated olefin units, and aromatic vinyl units.
[0012] The composition preferably contains silica, and the mixing amount (parts by mass) of silica relative to 100 parts by mass of the rubber component / average primary particle size (nm) of silica is preferably 1 to 1,000.
[0013] The composition preferably contains carbon black, and the ratio of the amount (parts by mass) of carbon black to 100 parts by mass of the rubber component / average primary particle size (nm) of carbon black is preferably 1 to 1,000.
[0014] The composition is preferably for use in a tire tread.
[0015] The present invention also relates to a tire having tire components using the above composition.
[0016] The tire component is preferably a tread. Effect of the Invention
[0017] According to the present invention, a plasticizer for resins and / or elastomers is provided which has a group whose interaction with an antifreeze solution changes depending on temperature, and the lower critical solution temperature of the group is −20° C. to 20° C., so that tire performance can be changed in the temperature range required for tires, and a tire composition can be produced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] (Plasticizer) The plasticizer of the present invention is a plasticizer for resins and / or elastomers that has a group whose interaction with an antifreeze solution changes depending on temperature, and the lower critical solution temperature of the group is −20° C. to 20° C. This makes it possible to change tire performance in the temperature range required for tires, and also makes it possible to produce a tire composition.
[0019] The reason why such an effect is obtained is not entirely clear, but is presumed to be as follows. Since the plasticizer of the present invention has a group whose interaction with antifreeze changes with temperature change, it is presumed that the hydrophilicity changes with temperature change, which changes the compatibility with other components in the composition, and thus the tire performance changes in response to temperature change. Furthermore, since the lower critical solution temperature of the group is −20° C. to 20° C., the tire performance can be changed in the temperature range required for tires. Specifically, the tire functions as a hydrophobic plasticizer at temperatures higher than the lower critical solution temperature of the group, and functions as a hydrophilic plasticizer at temperatures lower than the lower critical solution temperature of the group, thereby changing the tire performance with the above temperature range as the boundary, and changing the tire performance in the temperature range required for tires (for example, −40 to 40° C.). In addition, since the lower critical solution temperature is within the above range, the effect on the resin and / or elastomer, which are the framework components of the tire composition, can be minimized, making it possible to produce a tire composition. The plasticizer of the present invention can improve the overall performance, for example, fuel economy and wet grip performance.
[0020] In this specification, the plasticizer is a material that imparts plasticity to a resin and / or elastomer, and is a concept that includes liquid plasticizers (plasticizers that are liquid (liquid) at 25°C) and solid plasticizers (plasticizers that are solid at 25°C). Specifically, it is a component that can be extracted from a composition using acetone. These may be used alone or in combination of two or more types.
[0021] In this specification, the group whose interaction with the antifreeze solution changes with a change in temperature may be any group whose interaction with the antifreeze solution changes with a change in temperature, and is preferably a group whose interaction with the antifreeze solution changes reversibly with a change in temperature. More specifically, it may be any group whose hydrophilicity changes with a change in temperature, and is preferably a group whose hydrophilicity changes reversibly with a change in temperature. More specifically, it may be any group whose hydrophilicity changes at a relatively low temperature (preferably within a preferred temperature range of the phase transition temperature of the temperature-responsive polymer described later) with a change in temperature, and is preferably a group whose hydrophilicity changes reversibly with a change in temperature at a relatively low temperature (preferably within a preferred temperature range of the phase transition temperature of the temperature-responsive polymer described later).
[0022] An example of a group whose interaction (hydrophilicity) with an antifreeze solution changes reversibly with a change in temperature is a temperature-responsive polymer (temperature-responsive polymer group). That is, a plasticizer having a group whose interaction with an antifreeze solution changes with a change in temperature means, for example, a plasticizer having a group formed by a temperature-responsive polymer. Examples of the plasticizer include a plasticizer to which a temperature-responsive polymer is grafted, a plasticizer having a temperature-responsive polymer unit in the main chain, and a plasticizer having a temperature-responsive polymer block in the main chain. These may be used alone or in combination of two or more.
[0023] Thermoresponsive polymers are materials that undergo reversible conformational changes in polymer chains associated with hydration and dehydration in response to temperature changes in water, and their hydrophilicity and hydrophobicity change reversibly with temperature changes. This reversible change is known to be due to the molecular structure that has hydrophilic groups capable of hydrogen bonding and hydrophobic groups that are not compatible with water within a single molecule. The inventors have discovered that the hydrophilicity and hydrophobicity of a temperature-responsive polymer reversibly change with temperature not only in water, but also in an antifreeze solution (i.e., at low temperatures) and in a composition containing a resin and / or an elastomer.
[0024] Known temperature-responsive polymers include polymers that exhibit a lower critical solution temperature (LCST, also called lower critical solution temperature or lower critical dissolution temperature) in water and polymers that exhibit an upper critical solution temperature (UCST, also called upper critical solution temperature or upper critical dissolution temperature) in water. These may be used alone or in combination of two or more kinds. The thermoresponsive polymer reversibly changes its hydrophilicity and hydrophobicity in antifreeze at the same temperature as in water. For example, PNIPAM, which has an LCST of about 32°C in water, also has an LCST of about 32°C in antifreeze.
[0025] Polymers that exhibit LCST exhibit a phase transition that is reversible at the LCST. At temperatures above the LCST, the intramolecular or intermolecular hydrophobic bonds strengthen, causing the polymer chains to aggregate and become hydrophobic. At temperatures below the LCST, on the other hand, the polymer chains bind water molecules, become hydrated, and become hydrophilic. Thus, the polymer shows a reversible phase transition behavior at the LCST. Conversely, polymers that exhibit UCST become hydrophobic and insoluble at temperatures lower than UCST, but become hydrophilic and soluble at temperatures higher than UCST. In this way, they exhibit reversible phase transition behavior at the UCST boundary. It is believed that this is because the polymers have multiple amide groups in their side chains, and hydrogen bonds between the side chains act as a driving force to create intermolecular forces, resulting in UCST-type behavior.
[0026] When the group whose interaction with the antifreeze changes reversibly with a change in temperature is a polymer that exhibits an LCST, the glass transition temperature changes as a result of the group becoming incompatible with other components in the composition due to a change in temperature, and tire performance (e.g., wet grip performance, ice grip performance) can be changed in response to a change in temperature. In the plasticizer, the group whose interaction with the antifreeze solution changes reversibly with temperature change is preferably a polymer that exhibits an LCST, i.e., the group whose interaction with the antifreeze solution changes with temperature change is preferably a group that exhibits a lower critical solution temperature in the antifreeze solution. In this specification, a group exhibiting a lower critical solution temperature (LCST) in an antifreeze means a group that exhibits a lower critical solution temperature in an antifreeze when a group contained in a plasticizer is cleaved from the plasticizer and the cleaved group (polymer) is introduced into the antifreeze. Similarly, in this specification, a group that exhibits an upper critical solution temperature (UCST) in an antifreeze means a group that exhibits an upper critical solution temperature in an antifreeze when a group contained in a plasticizer is cleaved from the plasticizer and the cleaved group (polymer) is introduced into the antifreeze.
[0027] In this specification, antifreeze liquid refers to a liquid consisting of methanol and water, which is obtained by adding methanol in an amount 9 times the volume of water and mixing at 25° C. for 30 minutes.
[0028] The group (polymer) exhibiting LCST will be described below. The group (polymer) exhibiting the LCST may be used alone or in combination of two or more kinds. The group (polymer) exhibiting LCST is not particularly limited as long as it is a group (polymer) exhibiting LCST, but poly(alkyl vinyl ether) is preferred, and a group represented by the following formula (I) is more preferred. A group represented by the following formula (II) is also preferred. This tends to produce more favorable effects. These may be used alone or in combination of two or more. [ka] (In the formula, n represents an integer of 1 to 1000, R 1 , R 2 and R 3 each independently represents a hydrogen atom or a hydrocarbyl group.
[0029] n is preferably 3 or more, more preferably 5 or more, even more preferably 10 or more, particularly preferably 20 or more, and is preferably 500 or less, more preferably 300 or less, even more preferably 150 or less, particularly preferably 80 or less, most preferably 40 or less, and even more preferably 30 or less. Within the above range, the effect tends to be better obtained.
[0030] R 1 The number of carbon atoms in the hydrocarbyl group is not particularly limited, but is preferably 1 or more, more preferably 2 or more, and is preferably 20 or less, more preferably 18 or less, even more preferably 14 or less, particularly preferably 10 or less, most preferably 6 or less, and most preferably 4 or less. When it is within the above range, the effect tends to be better obtained.
[0031] R 2 and R 3 The number of carbon atoms in the hydrocarbyl group is not particularly limited, but is preferably 1 or more and preferably 5 or less, more preferably 3 or less, even more preferably 2 or less, and particularly preferably 1. When it is within the above range, the effect tends to be better obtained.
[0032] R 1 , R 2 and R 3Examples of the hydrocarbyl group include alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, n-pentyl, neopentyl, isopentyl, and n-hexyl groups; cycloalkyl groups such as cyclohexyl groups; and aryl groups such as methylphenyl and ethylphenyl groups. Among these, alkyl groups and cycloalkyl groups are preferred, and alkyl groups are more preferred.
[0033] R 1 is an alkyl group, R 2 and R 3 is preferably a hydrogen atom, and R 1 is an ethyl group, R 2 and R 3 is more preferably a hydrogen atom.
[0034] Examples of the group represented by the above formula (I) include poly(methyl vinyl ether), poly(ethyl vinyl ether), poly(propyl vinyl ether), poly(butyl vinyl ether), poly(pentenyl ether), poly(hexyl vinyl ether), poly(heptyl vinyl ether), poly(octyl ether), and the like. These may be used alone or in combination of two or more. Among them, poly(ethyl vinyl ether) (PEVE) is preferable. As a result of intensive research by the present inventors, it was found that PEVE exhibits an LCST at -10°C to +10°C. That is, a plasticizer having a PEVE group has a surface property of hydrophilic / hydrophobicity that changes significantly at -10°C to +10°C. Therefore, by using the plasticizer having a PEVE group as a plasticizer for resins and / or elastomers, tire performance can be changed in the temperature range required for tires, and a tire composition can be produced.
[0035] Next, the group represented by the following formula (II) will be described. [ka] (In the formula, n represents an integer of 1 to 1000, R 4represents an n-butyl group or a tert-butyl group, R 5 represents a hydrogen atom or a hydrocarbyl group.
[0036] n is preferably 3 or more, more preferably 5 or more, even more preferably 10 or more, particularly preferably 20 or more, and is preferably 500 or less, more preferably 300 or less, even more preferably 150 or less, particularly preferably 80 or less, most preferably 40 or less, and even more preferably 30 or less. Within the above range, the effect tends to be better obtained.
[0037] R 4 is an n-butyl group or a tert-butyl group, with a tert-butyl group being preferred.
[0038] R 5 The number of carbon atoms in the hydrocarbyl group is not particularly limited, but is preferably 1 or more, preferably 5 or less, more preferably 3 or less, even more preferably 2 or less, and particularly preferably 1. When it is within the above range, the effect tends to be better obtained.
[0039] R 5 The hydrocarbyl group of R 1 , R 2 and R 3 Among them, an alkyl group is preferable.
[0040] R 5 The hydrocarbyl groups may be branched or unbranched.
[0041] R 5 is preferably a hydrogen atom or an alkyl group, and more preferably a hydrogen atom.
[0042] R 4 is an n-butyl group or a tert-butyl group, R 5 is preferably a hydrogen atom, and R 4 is a tert-butyl group, R 5 It is more preferable that is a hydrogen atom.
[0043] Examples of the group represented by the above formula (II) include poly(Nn-butylacrylamide), poly(N-tert-butylacrylamide), poly(Nn-butylmethacrylamide), and poly(N-tert-butylmethacrylamide). These may be used alone or in combination of two or more. Among them, poly(Nn-butylacrylamide) and poly(N-tert-butylacrylamide) are preferred. As a result of intensive research by the present inventors, it was found that poly(Nn-butylacrylamide) and poly(N-tert-butylacrylamide) exhibit LCST at -10°C to +10°C. That is, a plasticizer having a poly(Nn-butylacrylamide) group or a poly(N-tert-butylacrylamide) group has a hydrophilic / hydrophobic surface property that changes significantly at -10°C to +10°C, so that by using the plasticizer as a plasticizer for resins and / or elastomers, tire performance can be changed in the temperature range required for tires, and a tire composition can be produced.
[0044] Examples of groups that exhibit LCST other than those mentioned above include a copolymer of N-isopropylacrylamide and butyl acrylate, a block copolymer of N-isopropylacrylamide and polyethylene oxide, a copolymer of N-isopropylacrylamide and a fluorine monomer, a copolymer of 2-methoxyethyl acrylate and N,N-dimethylacrylamide, biotin-immobilized temperature-responsive magnetic particles (particles obtained by reacting N-acryloylglycinamide, methacrylated magnetic particles, and a biotin monomer), a copolymer of ethylene oxide and propylene oxide, a monoamine derivative of a copolymer of ethylene oxide and propylene oxide, a polyethylene oxide-polypropylene oxide-polyethylene oxide block copolymer, maltopentaose-modified polypropylene oxide, a copolymer of 2-methoxyethyl acrylate and acryloylmorpholine, a copolymer of 2-methoxyethyl acrylate and N-vinylpyrrolide, Examples of the copolymer include copolymers of 2-methoxyethyl acrylate and 2-hydroxyethyl acrylate, copolymers of 2-methoxyethyl acrylate and methoxytriethylene glycol acrylate, poly[2-(2-ethoxyethoxy)ethyl acrylate], poly(2-(2-ethoxyethoxy)ethyl acrylate-co-2-(methoxyethoxy)ethyl methacrylate, copolymers of N-vinyl caprolactam and hydroxyethyl methacrylate, copolymers of methyl vinyl ether and hydroxyethyl methacrylate, poly(1-n-propyl-3-vinyl-2-imidazolidone), poly(N-vinyl-2-imidazolidone compound), copolymers of 2-hydroxyethyl vinyl ether and vinyl acetate, copolymers of diethylene glycol monovinyl ether and vinyl acetate, magnetic nanoparticles, polystyrene having an amino group, and glycoluril polymers. These may be used alone or in combination of two or more.
[0045] Incidentally, as the group whose interaction with the antifreeze solution changes depending on the temperature change, the temperature-responsive polymer group, the group (polymer) exhibiting LCST, poly(alkyl vinyl ether), and the group represented by the above formula (I), the following compounds (groups) are preferably excluded. Polyvinyl methyl ether (Poly(methyl vinyl ether))
[0046] In addition, as plasticizers for resins and / or elastomers having a group whose interaction with the antifreeze solution changes depending on the temperature, it is preferable to exclude the following plasticizers. (1) 11.32 g of N-isopropylacrylamide (NIPAM monomer) was added to a nitrogen-substituted glass flask, and 25 mL of toluene was added and stirred at room temperature for 30 minutes to obtain a uniform solution. Then, 1.10 g of 2,2'-azobis(isobutyronitrile) (AIBN) was added and the mixture was refluxed for 3 hours to react. The reaction solution was cooled to 40°C, and then 11.32 g of styrene acrylic resin (PS, ARUFON UH-2170 (softening point: 80°C) manufactured by Toagosei Co., Ltd.) and 25 mL of toluene were added and refluxed for 3 hours to react. After that, the toluene solvent was removed from the reaction solution using a rotary evaporator, and the remaining dried product was dried under reduced pressure at a vacuum of 0.1 Pa or less at 80°C for 8 hours to obtain a plasticizer (PNIPAM-PS resin). (2) 11.32 g of N-isopropylacrylamide (NIPAM monomer) was added to a nitrogen-substituted glass flask, and 25 mL of toluene was added and stirred at room temperature for 30 minutes to obtain a uniform solution. Then, 1.10 g of 2,2'-azobis(isobutyronitrile) (AIBN) was added, and the mixture was refluxed for 3 hours to cause a reaction. The reaction solution was cooled to 40°C, and then 11.32 g of maleic acid-modified liquid polybutadiene (Ricon 130MA8 (maleic acid-modified liquid BR, Mw: 2700) manufactured by Clay Valley) and 25 mL of toluene were added, and the mixture was refluxed for 3 hours to cause a reaction. After that, the toluene solvent was distilled off from the reaction solution using a rotary evaporator, and the remaining dried product was dried under reduced pressure at a reduced pressure of 0.1 Pa or less at 80°C for 8 hours to obtain a plasticizer (PNIPAM-BR).
[0047] Furthermore, as the group whose interaction with the antifreeze solution changes depending on the temperature change, the temperature responsive polymer group, and the group (polymer) showing LCST, the following compounds (groups) are preferably excluded. A group represented by the following formula (A): [ka] (In the formula, n represents an integer of 1 to 1000, R 1 , R 2 and R 3 each independently represents a hydrogen atom or a hydrocarbyl group; R 1 and R 2 At least one of is not a hydrogen atom, and R 1 and R 2 may form a ring structure.) Poly(N-vinyl-caprolactam) represented by the following formula (II) Poly(2-alkyl-2-oxazoline) represented by the following formula (III): Alkyl-substituted cellulose Poly(N-ethoxyethylacrylamide) Poly(N-ethoxyethyl methacrylamide) Poly(N-tetrahydrofurfuryl acrylamide) Poly(N-tetrahydrofurfuryl methacrylamide) Polyvinyl methyl ether Poly[2-(dimethylamino)ethyl methacrylate] Poly(3-ethyl-N-vinyl-2-pyrrolidone) Hydroxybutyl Chitosan Polyoxyethylene (20) Sorbitan Monostearate Polyoxyethylene (20) Sorbitan Monolaurate Polyoxyethylene (20) sorbitan monooleate Poly(ethylene glycol) methacrylates containing 2 to 6 ethylene glycol units Polyethylene glycol-co-polypropylene glycol Ethoxylated Iso-C 13 H 27 -alcohol Polyethylene glycol containing 4 to 50 ethylene glycol units Polypropylene glycol having 4 to 30 propylene glycol units Monomethyl, dimethyl, monoethyl, and diethyl ethers of polyethylene glycols containing 4 to 50 ethylene glycol units Monomethyl, dimethyl, monoethyl, and diethyl ethers of polypropylene glycol having 4 to 50 propylene glycol units. [ka] (In formulas (II) to (III), n is the same as n in formula (A) above. In formula (III), R is an alkyl group selected from an n-propyl group, an isopropyl group, or an ethyl group.)
[0048] Furthermore, as the group whose interaction with the antifreeze solution changes depending on the temperature change, the temperature responsive polymer group, and the group (polymer) showing LCST, the following compounds (groups) are preferably excluded. Poly(N-substituted (meth)acrylamide) Poly(N-vinyl-caprolactam) represented by the following formula (II) Poly(2-alkyl-2-oxazoline) represented by the following formula (III): Alkyl-substituted cellulose Poly(N-ethoxyethylacrylamide) Poly(N-ethoxyethyl methacrylamide) Poly(N-tetrahydrofurfuryl acrylamide) Poly(N-tetrahydrofurfuryl methacrylamide) Polyvinyl methyl ether Poly[2-(dimethylamino)ethyl methacrylate] Poly(3-ethyl-N-vinyl-2-pyrrolidone) Hydroxybutyl Chitosan Polyoxyethylene (20) Sorbitan Monostearate Polyoxyethylene (20) Sorbitan Monolaurate Polyoxyethylene (20) sorbitan monooleate Poly(ethylene glycol) methacrylates containing 2 to 6 ethylene glycol units Polyethylene glycol-co-polypropylene glycol Ethoxylated Iso-C 13 H 27 -alcohol Polyethylene glycol containing 4 to 50 ethylene glycol units Polypropylene glycol having 4 to 30 propylene glycol units Monomethyl, dimethyl, monoethyl, and diethyl ethers of polyethylene glycols containing 4 to 50 ethylene glycol units Monomethyl, dimethyl, monoethyl, and diethyl ethers of polypropylene glycol having 4 to 50 propylene glycol units. [ka] (In formulas (II) to (III), n is the same as n in formula (A) above. In formula (III), R is an alkyl group selected from an n-propyl group, an isopropyl group, or an ethyl group.)
[0049] The weight average molecular weight of the group (the group formed by the temperature-responsive polymer) whose interaction with the antifreeze solution changes with temperature change is preferably 50 or more, more preferably 560 or more, and even more preferably 1130 or more, and is preferably 57000 or less, more preferably 34000 or less, and even more preferably 17000 or less. Within the above range, the effect tends to be better obtained.
[0050] The phase transition temperature (lower critical solution temperature (LCST) or upper critical solution temperature (UCST), particularly LCST) of the temperature-responsive polymer is −20° C. or higher and 20° C. or lower, preferably 10° C. or lower. Within the above range, the effect tends to be better obtained. In this specification, the phase transition temperature of a temperature-responsive polymer can be easily measured by preparing a 1 mass % polymer / antifreeze solution using a 90 v / v % aqueous methanol solution (antifreeze), storing the solution in a freezer at a specified temperature (e.g., −20° C.) or refrigerator (e.g., +5° C.) for one hour or more, and checking the turbidity at each temperature. Here, the temperature-responsive polymer refers to a temperature-responsive polymer group (temperature-responsive polymer) obtained by cleaving a temperature-responsive polymer group possessed by a plasticizer from the plasticizer. The 90 v / v % aqueous methanol solution is a liquid consisting of methanol and water, and is obtained by adding 9 times the volume of methanol to water and mixing at 25° C. for 30 minutes.
[0051] The content of the group (group formed by the temperature-responsive polymer) whose interaction with the antifreeze solution changes depending on the temperature change in 100% by mass of the plasticizer is preferably 0.1% by mass or more, more preferably 1% by mass or more, even more preferably 5% by mass or more, particularly preferably 10% by mass or more, most preferably 20% by mass or more, even more preferably 30% by mass or more, even more preferably 40% by mass or more, and preferably 99% by mass or less, more preferably 80% by mass or less, even more preferably 70% by mass or less, particularly preferably 60% by mass or less, and most preferably 50% by mass or less. Within the above range, the effect tends to be better obtained.
[0052] As described above, a plasticizer having a group whose interaction with the antifreeze solution changes depending on the temperature means, for example, a plasticizer having a group formed by a temperature-responsive polymer, that is, a plasticizer to which a group formed by a temperature-responsive polymer is bonded. Specifically, the plasticizer having a group whose interaction with the antifreeze solution changes with temperature change is any of oils, ester-based plasticizers, and liquid or solid resins (hereinafter collectively referred to as oils, etc.), and has a group formed by a temperature-responsive polymer. These may be used alone or in combination of two or more kinds.
[0053] Conventionally used oils and the like usually do not have a group formed by a temperature-responsive polymer. Therefore, if a commercially available product is available as the plasticizer, it may be used, but the plasticizer may be produced using a known synthesis technique. For example, the plasticizer may be produced by referring to JP-A-2005-314419, JP-A-2016-505679, JP-A-2015-531672, JP-A-2003-252936, JP-A-2004-307523, etc.
[0054] The plasticizer may be produced, for example, by synthesizing the plasticizer using a monomer component capable of forming a temperature-responsive polymer unit according to a known method. For example, after polymerizing the plasticizer by cationic polymerization, ethyl vinyl ether (EVE), a monomer constituting the temperature-responsive polymer PEVE, is added, and the addition of the temperature-responsive polymer PEVE to the plasticizer structure can be confirmed by the increase in molecular weight.
[0055] As another method for producing the above-mentioned plasticizer, for example, a plasticizer to which PEVE is added can be synthesized by radically polymerizing PEVE according to a known method and reacting it with a plasticizer component capable of radical addition. That is, the plasticizer can be synthesized using a monomer component capable of forming a temperature-responsive polymer unit. This allows the production of a plasticizer having a temperature-responsive polymer unit in the main chain. For example, to produce a plasticizer having a PEVE unit in the main chain, ethyl vinyl ether, a monomer that constitutes PEVE, is used as a monomer component and stirred with a radical generator such as AIBN to cause radical polymerization, followed by a radical addition reaction with a liquid or solid resin that has a double bond or a carboxylic acid group that can react with radicals, thereby producing a resin having a PEVE unit in the main chain. Furthermore, by appropriately adjusting the polymerization method, random copolymers and block copolymers can be produced, and this technology can also be used to produce plasticizers having a temperature-responsive polymer block in the main chain.
[0056] The termini of the temperature-responsive polymer will now be described. In the case of a plasticizer to which a temperature-responsive polymer has been added, one end of the temperature-responsive polymer is the main chain or a bond to the main chain, and the other end is usually a hydrogen atom, but may also be bonded to a polymerization initiator such as azobisisobutyronitrile (AIBN). In the case of a plasticizer having a temperature-responsive polymer unit in the main chain or a plasticizer having a temperature-responsive polymer block in the main chain, the end of the temperature-responsive polymer is another structural unit or a bond to another structural unit, and when the temperature-responsive polymer unit (temperature-responsive polymer block) is present at the molecular end, one end is usually a hydrogen atom, but may also be bonded to a polymerization initiator such as azobisisobutyronitrile (AIBN).
[0057] In the following, oils, ester plasticizers, liquid resins, and solid resins (collectively referred to as oils, etc.) into which a group (a group formed by a temperature-responsive polymer) whose interaction with the antifreeze solution changes with temperature change will be described. These may be used alone or in combination of two or more. The oils, etc. into which the above group is introduced are not particularly limited and may be any oil as long as it has plasticity, and for example, those generally used as tire compounds can be used. As the oils, etc. into which the above group is introduced, oils, liquid resins, and solid resins are preferred, liquid resins and solid resins are more preferred, and solid resins are even more preferred.
[0058] The oil is not particularly limited, and may be a conventionally known oil such as paraffin-based process oil, aromatic process oil, naphthenic process oil, low PCA (polycyclic aromatic) process oil such as TDAE and MES, vegetable oil, and mixtures thereof. These may be used alone or in combination of two or more. Among them, aromatic process oil is preferred. Specific examples of the aromatic process oil include Diana Process Oil AH series manufactured by Idemitsu Kosan Co., Ltd.
[0059] As the oil, for example, products from Idemitsu Kosan Co., Ltd., Sankyo Yuka Kogyo Co., Ltd., Japan Energy Co., Ltd., Orisoi Co., Ltd., H&R Co., Ltd., Toyokuni Oil Mills Co., Ltd., Showa Shell Sekiyu K.K., Fuji Kosan Co., Ltd., etc. can be used.
[0060] Examples of the ester-based plasticizer include the above-mentioned vegetable oils, synthetic products such as glycerin fatty acid monoesters, glycerin fatty acid diesters, and glycerin fatty acid triesters, processed vegetable oils, and phosphoric acid esters (phosphate-based esters, mixtures thereof, etc.). These may be used alone or in combination of two or more.
[0061] As the ester-based plasticizer, for example, a fatty acid ester represented by the following formula can be suitably used. [ka] (In the formula, R 11 R represents a linear or branched alkyl group having 1 to 8 carbon atoms, a linear or branched alkenyl group having 1 to 8 carbon atoms, or a linear or branched alkyl group having 2 to 6 carbon atoms substituted with 1 to 5 hydroxyl groups. 12 represents an alkyl group or alkenyl group having 11 to 21 carbon atoms.
[0062] R 11 Examples of R include a methyl group, an ethyl group, a 2-ethylhexyl group, an isopropyl group, an octyl group, and groups in which these groups are substituted with 1 to 5 hydroxyl groups. 12 Examples of the alkyl group include linear or branched alkyl groups and alkenyl groups such as lauryl group, myristyl group, palmityl group, stearyl group, and oleyl group.
[0063] Examples of fatty acid esters include alkyl oleates, alkyl stearates, alkyl linoleates, and alkyl palmitates. Among these, alkyl oleates (methyl oleate, ethyl oleate, 2-ethylhexyl oleate, isopropyl oleate, octyl oleate, and the like) are preferred. In this case, the content of alkyl oleates in 100% by mass of fatty acid ester is preferably 80% by mass or more.
[0064] Examples of fatty acid esters include fatty acid monoesters and fatty acid diesters of fatty acids (oleic acid, stearic acid, linoleic acid, palmitic acid, etc.) and alcohols (ethylene glycol, glycerol, trimethylolpropane, pentaerythritol, erythritol, xylitol, sorbitol, dulcitol, mannitol, inositol, etc.). Among these, oleic acid monoesters are preferred. In this case, the content of oleic acid monoesters in the total amount of fatty acid monoesters and fatty acid diesters (100% by mass) is preferably 80% by mass or more.
[0065] As the ester-based plasticizer, a phosphoric ester can also be suitably used. The phosphate ester is preferably a compound having 12 to 30 carbon atoms, and among them, trialkyl phosphate having 12 to 30 carbon atoms is preferable. The number of carbon atoms in the trialkyl phosphate means the total number of carbon atoms in the three alkyl groups, and the three alkyl groups may be the same or different. Examples of the alkyl group include linear or branched alkyl groups, and may contain heteroatoms such as oxygen atoms or be substituted with halogen atoms such as fluorine, chlorine, bromine, and iodine.
[0066] Examples of the phosphoric acid ester include known phosphoric acid ester-based plasticizers such as mono-, di-, or triester of phosphoric acid with a monoalcohol having 1 to 12 carbon atoms or its (poly)oxyalkylene adduct, a compound in which one or two of the alkyl groups of the trialkyl phosphate are substituted with phenyl groups, etc. Specific examples include tris(2-ethylhexyl) phosphate, trimethyl phosphate, triethyl phosphate, tributyl phosphate, trioctyl phosphate, triphenyl phosphate, tricresyl phosphate, trixylenyl phosphate, cresyl diphenyl phosphate, 2-ethylhexyl diphenyl phosphate, and tris(2-butoxyethyl) phosphate.
[0067] Examples of solid resins include terpene resins (including rosin resins), styrene resins, C5 resins, C9 resins, C5 / C9 resins, coumarone-indene resins (including coumarone and indene simple resins), olefin resins, urethane resins, acrylic resins, pt-butylphenol acetylene resins, and dicyclopentadiene resins (DCPD resins), which are solid at 25°C. The above resins may be hydrogenated. These may be one type or a mixture of two or more types, or the resin itself may be a copolymer of monomer components of multiple origins. Among these, styrene resins and terpene resins are preferred, and styrene resins are more preferred.
[0068] Examples of solid resins that can be used include products from Maruzen Petrochemical Co., Ltd., Sumitomo Bakelite Co., Ltd., Yasuhara Chemical Co., Ltd., Tosoh Corporation, Rutgers Chemicals, BASF, Arizona Chemical Company, Nippon Paint Chemical Co., Ltd., Nippon Shokubai Co., Ltd., JXTG Nippon Oil & Energy Corporation, Arakawa Chemical Industries, Ltd., and Taoka Chemical Co., Ltd.
[0069] The softening point of the solid resin is preferably 30° C. or higher, more preferably 60° C. or higher, even more preferably 80° C. or higher, and is preferably 200° C. or lower, more preferably 160° C. or lower, even more preferably 140° C. or lower, and particularly preferably 120° C. or lower. By keeping it within the above range, the effect tends to be more suitably obtained. In this specification, the softening point of a resin is the temperature at which the ball drops when the softening point as specified in JIS K 6220-1:2001 is measured using a ring and ball softening point tester.
[0070] The terpene resin is not particularly limited as long as it is a resin having a unit derived from a terpene compound, and examples thereof include polyterpene (a resin obtained by polymerizing a terpene compound), terpene aromatic resin (a resin obtained by copolymerizing a terpene compound and an aromatic compound), and aromatic modified terpene resin (a resin obtained by modifying a terpene resin with an aromatic compound). Among these, polyterpene is preferred.
[0071] The terpene compound is (C 5 H 8 ) n The hydrocarbons and their oxygen-containing derivatives represented by the composition: monoterpenes (C 10 H 16 ), sesquiterpenes (C 15 H 24 ), diterpenes (C 20 H 32 ), and examples thereof include α-pinene, β-pinene, dipentene, limonene, myrcene, alloocimene, ocimene, α-phellandrene, α-terpinene, γ-terpinene, terpinolene, 1,8-cineole, 1,4-cineole, α-terpineol, β-terpineol, and γ-terpineol. The terpene compounds also include resin acids (rosin acids) such as abietic acid, neoabietic acid, palustric acid, levopimaric acid, pimaric acid, and isopimaric acid. In other words, the terpene resins include rosin resins whose main component is rosin acid obtained by processing pine resin. Examples of rosin resins include naturally occurring rosin resins (polymerized rosins) such as gum rosin, wood rosin, and tall oil rosin, as well as modified rosin resins such as maleic acid modified rosin resin and rosin modified phenolic resin, rosin esters such as rosin glycerin ester, and disproportionated rosin resins obtained by disproportionating rosin resin. As the terpene compound, α-pinene and β-pinene are preferable, and β-pinene is more preferable. That is, as the polyterpene, polyα-pinene and polyβ-pinene are preferable, and polyβ-pinene is more preferable.
[0072] The aromatic compound is not particularly limited as long as it is a compound having an aromatic ring, and examples thereof include phenolic compounds such as phenol, alkylphenol, alkoxyphenol, and unsaturated hydrocarbon group-containing phenol; naphthol compounds such as naphthol, alkylnaphthol, alkoxynaphthol, and unsaturated hydrocarbon group-containing naphthol; styrene derivatives such as styrene, alkylstyrene, alkoxystyrene, and unsaturated hydrocarbon group-containing styrene; etc. Among these, styrene is preferred.
[0073] The styrene-based resin is a polymer using a styrene-based monomer as a constituent monomer, and examples thereof include polymers obtained by polymerizing a styrene-based monomer as a main component (50% by mass or more, preferably 80% by mass or more). Specifically, examples thereof include homopolymers obtained by polymerizing each of styrene-based monomers (styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, α-methylstyrene, p-methoxystyrene, p-tert-butylstyrene, p-phenylstyrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, etc.) alone, copolymers obtained by copolymerizing two or more kinds of styrene-based monomers, and copolymers of a styrene-based monomer and another monomer that can be copolymerized therewith. Among these, homopolymers obtained by polymerizing a styrene-based monomer alone are preferred.
[0074] Examples of the other monomers include acrylonitriles such as acrylonitrile and methacrylonitrile, unsaturated carboxylic acids such as acrylics and methacrylic acid, unsaturated carboxylic acid esters such as methyl acrylate and methyl methacrylate, dienes such as chloroprene and butadiene-isoprene, olefins such as 1-butene and 1-pentene, α,β-unsaturated carboxylic acids or acid anhydrides thereof such as maleic anhydride, and the like.
[0075] As the styrene-based resin, a homopolymer obtained by polymerizing a styrene-based monomer alone is preferable, a styrene homopolymer, an o-methylstyrene homopolymer, an m-methylstyrene homopolymer, a p-methylstyrene homopolymer, or an α-methylstyrene homopolymer is more preferable, and a styrene homopolymer or an α-methylstyrene homopolymer is even more preferable. As the styrene-based resin, α-methylstyrene-based resin (such as α-methylstyrene homopolymer or copolymer of α-methylstyrene and styrene) is also preferred.
[0076] As the liquid resin, a resin having a similar structure to the solid resin and a low softening point can be used. For example, terpene resins (including rosin resins) that are liquid at 25°C, styrene resins, C5 resins, C9 resins, C5 / C9 resins, coumarone-indene resins (including coumarone and indene simple resins), olefin resins, urethane resins, acrylic resins, pt-butylphenol acetylene resins, dicyclopentadiene resins (DCPD resins), and other resins that are liquid at 25°C can be mentioned. The above resins may be hydrogenated. These may be one type or a mixture of two or more types, or the resin itself may be a copolymer of monomer components of multiple origins. Among them, styrene resins are preferred. As the styrene resin, the same embodiment as the styrene resin described in the above solid resin is preferred. That is, the same embodiment as the styrene resin described in the above solid resin is preferred except for the molecular weight.
[0077] Further examples of the liquid resin include liquid farnesene-based polymers such as liquid (meaning liquid at 25° C., hereinafter the same) farnesene homopolymer, liquid farnesene-styrene copolymer, liquid farnesene-butadiene copolymer, liquid farnesene-styrene-butadiene copolymer, liquid farnesene-isoprene copolymer, and liquid farnesene-styrene-isoprene copolymer; liquid myrcene-based polymers such as liquid myrcene homopolymer, liquid myrcene-styrene copolymer, liquid myrcene-butadiene copolymer, liquid myrcene-styrene-butadiene copolymer, liquid myrcene-isoprene copolymer, and liquid myrcene-styrene-isoprene copolymer; liquid styrene-butadiene copolymer. Examples of the liquid diene polymers include liquid SBR, liquid butadiene polymer (liquid BR), liquid isoprene polymer (liquid IR), liquid styrene isoprene copolymer (liquid SIR), liquid styrene butadiene styrene block copolymer (liquid SBS block polymer), and liquid styrene isoprene styrene block copolymer (liquid SIS block polymer); liquid olefin polymers having olefin resins such as polyethylene and polypropylene as hard segments (hard phase) and rubber components as soft segments (soft phase); liquid ester polymers containing polyester as hard segments and polyether or polyester as soft segments; and the like. The terminals or main chains of these may be modified with polar groups. These may be used alone or in combination of two or more. Among these, liquid BR is preferred.
[0078] The weight average molecular weight of the liquid resin is preferably less than 100,000, more preferably 80,000 or less, and even more preferably 50,000 or less, and is preferably 5,000 or more, and more preferably 2,000 or more. Within the above range, the effect tends to be better.
[0079] Examples of the liquid resin that can be used include products from Maruzen Petrochemical Co., Ltd., Sumitomo Bakelite Co., Ltd., Yasuhara Chemical Co., Ltd., Tosoh Corporation, Rutgers Chemicals, BASF, Arizona Chemical Company, Nippon Paint Chemical Co., Ltd., Nippon Shokubai Co., Ltd., JXTG Nippon Oil & Energy Corporation, Arakawa Chemical Industries, Ltd., Taoka Chemical Co., Ltd., Sartomer Inc., and Kuraray Co., Ltd.
[0080] As the plasticizer having a group whose interaction with the antifreeze changes with temperature, a plasticizer having a group that exhibits a lower critical solution temperature in the antifreeze is preferable, a plasticizer having a poly(alkyl vinyl ether) is more preferable, a plasticizer having a group represented by the above formula (I) is even more preferable, and a plasticizer having a poly(ethyl vinyl ether) is particularly preferable. Furthermore, the plasticizer preferably has the above group introduced into a solid resin, more preferably has the above group introduced into a styrene-based resin, and even more preferably has the above group introduced into a styrene homopolymer or an α-methylstyrene homopolymer.
[0081] A plasticizer having a group whose interaction with the antifreeze changes with a change in temperature is a plasticizer for resins and / or elastomers.
[0082] Resins to which the plasticizer can be applied are not particularly limited, and in addition to the above-mentioned resins, examples of the resins to which the plasticizer can be applied include polycarbonate resins, polyester resins, polyester carbonate resins, polyphenylene ether resins, polyphenylene sulfide resins, polysulfone resins, polyether sulfone resins, polyarylene resins, polyamide resins, polyetherimide resins, polyacetal resins, polyvinyl acetal resins, polyketone resins, polyether ketone resins, polyether ether ketone resins, polyaryl ketone resins, polyether nitrile resins, liquid crystal resins, polybenzimide resins, and the like. Thermoplastic resins such as dazole resin, polyparabanic acid resin, polyolefin resin, vinyl chloride resin, cellulose resin, etc.; thermosetting resins such as epoxy resin, polyamideimide resin, thermosetting polyester resin (unsaturated polyester resin), silicone resin, urethane resin, (meth)acrylic resin, fluorine resin, phenol resin, urea resin, melamine resin, polyimide resin, alkyd resin, polyvinyl ester resin, polydiallyl phthalate resin, bismaleimide-triazine resin, furan resin, xylene resin, guanamine resin, maleic resin, polyether resin, etc. These may be used alone or in combination of two or more.
[0083] The elastomer to which the plasticizer can be applied is not particularly limited, and examples thereof include diene rubbers generally used as rubber components in tire compositions, such as isoprene rubber, butadiene rubber (BR), styrene butadiene rubber (SBR), styrene isoprene butadiene rubber (SIBR), ethylene propylene diene rubber (EPDM), chloroprene rubber (CR), and acrylonitrile butadiene rubber (NBR); acrylic rubbers such as butyl acrylate rubber, ethyl acrylate rubber, and octyl acrylate rubber, nitrile rubber, isobutylene rubber, methyl methacrylate-butyl acrylate block copolymer, ethylene-propylene copolymer (EPR), chlorosulfonated polyethylene, silicone rubber (millable type, room temperature vulcanization type), butyl rubber, fluororubber, and olefin-based thermoplastic elastomers. , styrene-based thermoplastic elastomers, vinyl chloride-based thermoplastic elastomers, urethane-based thermoplastic elastomers, polyamide-based thermoplastic elastomers, polyester-based thermoplastic elastomers, fluorine-based thermoplastic elastomers, styrene-isobutylene-styrene block copolymers (SIBS), styrene-isoprene-styrene block copolymers (SIS), styrene-isobutylene block copolymers (SIB), styrene-butadiene-styrene block copolymers (SBS), styrene-ethylene-butene-styrene block copolymers (SEBS), styrene-ethylene-propylene-styrene block copolymers (SEPS), styrene-ethylene-ethylene-propylene-styrene block copolymers (SEEPS), styrene-butadiene-butylene-styrene block copolymers (SBBS), etc. These may be used alone or in combination of two or more.
[0084] Among the resins and elastomers to which the above-mentioned plasticizers can be applied, rubber is preferred, diene-based rubber is more preferred, and isoprene-based rubber, BR, and SBR are even more preferred.
[0085] (composition) Next, a composition containing the above-mentioned plasticizer (a plasticizer having a group whose interaction with the antifreeze solution changes depending on the temperature) will be described. The plasticizer contained in the composition can be identified, for example, by the following method. Using a Soxhlet extraction apparatus, 100 mg of the composition is continuously extracted with tetrahydrofuran solvent at room temperature for 24 hours, and the extraction residue is fractionated based on molecular weight by gel permeation chromatography (GPC) or liquid chromatography-mass spectrometry (LC-MS), and the compounds can be identified by analyzing them by NMR. In the composition, the content of the plasticizer is preferably 0.1 parts by mass or more, more preferably 1 part by mass or more, even more preferably 3 parts by mass or more, particularly preferably 5 parts by mass or more, most preferably 10 parts by mass or more, and most preferably 20 parts by mass or more, and is preferably 200 parts by mass or less, more preferably 100 parts by mass or less, even more preferably 80 parts by mass or less, particularly preferably 60 parts by mass or less, and most preferably 50 parts by mass or less, relative to 100 parts by mass of the polymer component (preferably 100 parts by mass of the rubber component). Within the above range, the effect tends to be better obtained.
[0086] The plasticizer may be used together with a plasticizer other than the above plasticizer. Examples of the plasticizer other than the above plasticizer include oils into which the above-mentioned groups are introduced. These may be used alone or in combination of two or more. The total content of the plasticizers (the total content of the above plasticizers and plasticizers other than the above plasticizers) is the same as the content of the above plasticizers. The plasticizer content includes the amount of plasticizer contained in rubber (oil-extended rubber) and sulfur (oil-containing sulfur).
[0087] In the above composition, the polymer component that can be used includes resins and elastomers to which the above-mentioned plasticizers can be applied. These may be used alone or in combination of two or more. Among them, rubber is preferred, diene rubber is more preferred, and isoprene rubber, BR, and SBR are even more preferred.
[0088] Here, the polymer component (preferably the rubber component) is a polymer (rubber) having a weight average molecular weight (Mw) of preferably 200,000 or more, more preferably 350,000 or more. There is no particular upper limit for Mw, but it is preferably 4 million or less, more preferably 3 million or less. In this specification, Mw and number average molecular weight (Mn) can be determined by standard polystyrene conversion based on measurements obtained by gel permeation chromatography (GPC) (GPC-8000 series, manufactured by Tosoh Corporation, detector: differential refractometer, column: TSKGEL SUPERMULTIPORE HZ-M, manufactured by Tosoh Corporation).
[0089] The content of the diene rubber in 100% by mass of the polymer component (preferably 100% by mass of the rubber component) is preferably 20% by mass or more, more preferably 50% by mass or more, even more preferably 70% by mass or more, particularly preferably 80% by mass or more, and most preferably 90% by mass or more, and may be 100% by mass. When it is within the above range, the effect tends to be better obtained.
[0090] The polymer component may be an unmodified polymer or a modified polymer. The modified polymer may be a polymer (preferably a diene rubber) having a functional group that interacts with a filler such as silica. Examples of the modified polymer include a terminally modified polymer (terminally modified polymer having the above-mentioned functional group at the terminal) in which at least one terminal of the polymer has been modified with a compound (modifying agent) having the above-mentioned functional group, a main-chain modified polymer having the above-mentioned functional group in the main chain, a main-chain terminal-modified polymer having the above-mentioned functional group in the main chain and at least one terminal (for example, a main-chain terminal-modified polymer having the above-mentioned functional group in the main chain and at least one terminal modified with the above-mentioned modifying agent), and a terminal-modified polymer modified (coupled) with a polyfunctional compound having two or more epoxy groups in the molecule and having a hydroxyl group or an epoxy group introduced therein.
[0091] Examples of the functional group include an amino group, an amide group, a silyl group, an alkoxysilyl group, an isocyanate group, an imino group, an imidazole group, a urea group, an ether group, a carbonyl group, an oxycarbonyl group, a mercapto group, a sulfide group, a disulfide group, a sulfonyl group, a sulfinyl group, a thiocarbonyl group, an ammonium group, an imide group, a hydrazo group, an azo group, a diazo group, a carboxyl group, a nitrile group, a pyridyl group, an alkoxy group, a hydroxyl group, an oxy group, and an epoxy group. These functional groups may have a substituent. Among them, an amino group (preferably an amino group in which a hydrogen atom of an amino group is substituted with an alkyl group having 1 to 6 carbon atoms), an alkoxy group (preferably an alkoxy group having 1 to 6 carbon atoms), and an alkoxysilyl group (preferably an alkoxysilyl group having 1 to 6 carbon atoms) are preferred.
[0092] The SBR is not particularly limited, and for example, emulsion polymerized styrene butadiene rubber (E-SBR), solution polymerized styrene butadiene rubber (S-SBR), etc. can be used. These may be used alone or in combination of two or more kinds.
[0093] The styrene content of SBR is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, particularly preferably 20% by mass or more, and most preferably 25% by mass or more. The styrene content is preferably 60% by mass or less, more preferably 50% by mass or less, even more preferably 45% by mass or less, particularly preferably 40% by mass or less, and most preferably 35% by mass or less. Within the above range, the effect tends to be better obtained. In this specification, the styrene content of SBR is 1 It is calculated by H-NMR measurement.
[0094] As the SBR, for example, SBR manufactured and sold by Sumitomo Chemical Co., Ltd., JSR Corporation, Asahi Kasei Corporation, Nippon Zeon Co., Ltd., and the like can be used.
[0095] The SBR may be unmodified or modified. Modified SBR includes modified SBR having the same functional group as the modified polymer. Among them, modified SBR is preferable.
[0096] The BR is not particularly limited, and for example, high cis BR with a high cis content, BR containing syndiotactic polybutadiene crystals, BR synthesized using a rare earth catalyst (rare earth BR), etc. can be used. These may be used alone or in combination of two or more. Among them, high cis BR with a cis content of 90 mass% or more is preferred because it improves wear resistance. The cis content can be measured by infrared absorption spectroscopy.
[0097] The BR may be either unmodified or modified. The modified BR may be a modified BR having the same functional group as the modified polymer introduced therein.
[0098] As the BR, for example, products from Ube Industries, Ltd., JSR Corporation, Asahi Kasei Corporation, Zeon Corporation, etc. can be used.
[0099] Examples of isoprene-based rubber include natural rubber (NR), isoprene rubber (IR), modified NR, modified NR, and modified IR. Examples of NR include SIR20, RSS♯3, TSR20, and other rubbers that are common in the tire industry. Examples of IR include IR2200 and other rubbers that are common in the tire industry. Examples of modified NR include deproteinized natural rubber (DPNR), high-purity natural rubber (UPNR), and other rubbers. Examples of modified NR include epoxidized natural rubber (ENR), hydrogenated natural rubber (HNR), and grafted natural rubber. Examples of modified IR include epoxidized isoprene rubber, hydrogenated isoprene rubber, and grafted isoprene rubber. These may be used alone or in combination of two or more. Among these, NR is preferred.
[0100] The content of SBR in 100% by mass of the polymer component (preferably 100% by mass of the rubber component) is preferably 1% by mass or more, more preferably 10% by mass or more, even more preferably 40% by mass or more, and particularly preferably 60% by mass or more, and may be 100% by mass, but is preferably 90% by mass or less, more preferably 80% by mass or less. Within the above range, the effect tends to be better obtained.
[0101] The content of BR in 100% by mass of the polymer component (preferably 100% by mass of the rubber component) is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more. It may be 100% by mass, but is preferably 80% by mass or less, more preferably 50% by mass or less, and even more preferably 30% by mass or less. Within the above range, the effect tends to be better obtained.
[0102] The content of the isoprene-based rubber in 100% by mass of the polymer component (preferably 100% by mass of the rubber component) is preferably 1% by mass or more, more preferably 2% by mass or more, even more preferably 3% by mass or more, particularly preferably 4% by mass or more, and most preferably 10% by mass or more, and may be 100% by mass, but is preferably 80% by mass or less, more preferably 50% by mass or less, and even more preferably 30% by mass or less. Within the above range, the effect tends to be better obtained.
[0103] In addition, it is preferable that the rubber component contains a multi-component copolymer containing conjugated diene units, non-conjugated olefin units, and aromatic vinyl units, which tends to produce the desired effect.
[0104] In the multicomponent copolymer, the conjugated diene unit is a constituent unit derived from a conjugated diene compound, and examples of the conjugated diene compound include 1,3-butadiene, isoprene, 1,3-pentadiene, 2,3-dimethylbutadiene, 2-phenyl-1,3-butadiene, 1,3-hexadiene, etc. These may be used alone or in combination of two or more kinds, with 1,3-butadiene and isoprene being preferred, and 1,3-butadiene being more preferred.
[0105] In the multicomponent copolymer, the non-conjugated olefin unit is a structural unit derived from a non-conjugated olefin, and examples of the non-conjugated olefin include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, etc. These may be used alone or in combination of two or more kinds, with ethylene, propylene, and 1-butene being preferred, and ethylene being more preferred.
[0106] In the above multicomponent copolymer, the aromatic vinyl unit is a constituent unit derived from an aromatic vinyl compound, and examples of the aromatic vinyl compound include styrene, α-methylstyrene, 1-vinylnaphthalene, 3-vinyltoluene, ethylvinylbenzene, divinylbenzene, 4-cyclohexylstyrene, 2,4,6-trimethylstyrene, etc. These may be used alone or in combination of two or more kinds, but styrene and α-methylstyrene are preferred, and styrene is more preferred.
[0107] The multicomponent copolymer can be prepared, for example, by a method of copolymerizing a conjugated diene compound, a non-conjugated olefin, and an aromatic vinyl compound, or by a method of copolymerizing a conjugated diene compound and an aromatic vinyl compound, or a conjugated diene compound, a non-conjugated olefin, and an aromatic vinyl compound, and then converting a part of the conjugated diene units to non-conjugated olefin units by hydrogenation. That is, the multicomponent copolymer may be a copolymer of a conjugated diene compound, a non-conjugated olefin, and an aromatic vinyl compound, or a copolymer of a conjugated diene compound, a non-conjugated olefin, and an aromatic vinyl compound, or a hydrogenated copolymer (hydrogenated copolymer) of a copolymer of a conjugated diene compound, a non-conjugated olefin, and an aromatic vinyl compound. These may be used alone or in combination of two or more. Among them, a hydrogenated copolymer of a conjugated diene compound and an aromatic vinyl compound is preferred, and a hydrogenated styrene-butadiene copolymer (hydrogenated SBR) is more preferred.
[0108] In preparing the multicomponent copolymer, the polymerization method is not particularly limited, and may be random polymerization or block polymerization, with random polymerization being preferred.
[0109] When the multicomponent copolymer is a hydrogenated copolymer, the hydrogenation method and reaction conditions are not particularly limited, and hydrogenation may be performed by a known method and under known conditions. Usually, hydrogenation is performed at 20 to 150°C under a hydrogen pressure of 0.1 to 10 MPa in the presence of a hydrogenation catalyst. Other production methods and conditions are also not particularly limited, and for example, the contents described in the above-mentioned International Publication No. 2016 / 039005 can be applied.
[0110] When the multi-component copolymer is a hydrogenated copolymer, the hydrogenation rate is preferably 65 mol% or more, more preferably 70 mol% or more, even more preferably 80 mol% or more, and is preferably 95 mol% or less, more preferably 94.5 mol% or less, even more preferably 94 mol% or less, based on 100 mol% of the total conjugated diene units before hydrogenation. When it is within the above range, the effect tends to be better obtained. The hydrogenation rate is 1 It can be calculated from the spectral reduction rate of the unsaturated bond part of the spectrum obtained by measuring H-NMR.
[0111] In the above multicomponent copolymer, the content of the conjugated diene unit is preferably 1.9 mol% or more, more preferably 2.4 mol% or more, even more preferably 2.9 mol% or more, and is preferably 23.7 mol% or less, more preferably 16.9 mol% or less, even more preferably 10.7 mol% or less, based on 100 mol% of the total constituent units. Within the above range, the effect tends to be better obtained.
[0112] In the above multicomponent copolymer, the content of the non-conjugated olefin unit is preferably more than 65 mol%, more preferably 70 mol% or more, even more preferably 80 mol% or more, and is preferably less than 95 mol%, more preferably 94.5 mol% or less, even more preferably 94 mol% or less, based on the total number of constituent units being 100 mol%. Within the above range, the effect tends to be better obtained.
[0113] In the above multicomponent copolymer, the content of aromatic vinyl units is preferably 4 mol% or more, more preferably 8 mol% or more, and also preferably 45 mol% or less, more preferably 40 mol% or less, even more preferably 35 mol% or less, particularly preferably 25 mol% or less, and most preferably 20 mol% or less, based on 100 mol% of the total constituent units. When the content is within the above range, the effect tends to be better obtained.
[0114] The content of each of the structural units of the multicomponent copolymer is a value measured by NMR.
[0115] The weight average molecular weight (Mw) of the multicomponent copolymer is preferably 100,000 or more, more preferably 150,000 or more, even more preferably 200,000 or more, and particularly preferably 400,000 or more, and is preferably 2,000,000 or less, more preferably 1,500,000 or less, even more preferably 1,000,000 or less, and particularly preferably 600,000 or less. Within the above ranges, the effect tends to be better obtained.
[0116] The content of the multicomponent copolymer in 100% by mass of the rubber component is preferably 1% by mass or more, more preferably 10% by mass or more, even more preferably 40% by mass or more, and particularly preferably 60% by mass or more. It may be 100% by mass, but is preferably 90% by mass or less, more preferably 80% by mass or less. Within the above range, the effect tends to be better obtained.
[0117] The composition preferably contains silica as a filler (reinforcing filler). The silica is not particularly limited, and examples thereof include dry process silica (anhydrous silicic acid) and wet process silica (hydrated silicic acid). These may be used alone or in combination of two or more. Among them, wet process silica is preferred because it has a large number of silanol groups.
[0118] As the silica, for example, products manufactured by Degussa, Rhodia, Tosoh Silica Co., Ltd., Solvay Japan Co., Ltd., Tokuyama Corporation, etc. can be used.
[0119] The nitrogen adsorption specific surface area of silica (N 2 SA) is preferably 50m 2 / g or more, more preferably 150m 2 / g or more. 2 SA is preferably 300m 2 / g or less, more preferably 250m 2 / g or less, more preferably 200m 2 Within the above range, there is a tendency for the effect to be better obtained. In addition, the N of silica 2 SA can be measured in accordance with ASTM D3037-81.
[0120] The content of silica per 100 parts by mass of the polymer component (preferably 100 parts by mass of the rubber component) is preferably 0.1 parts by mass or more, more preferably 10 parts by mass or more, even more preferably 30 parts by mass or more, particularly preferably 50 parts by mass or more, and is preferably 200 parts by mass or less, more preferably 180 parts by mass or less, even more preferably 150 parts by mass or less, particularly preferably 120 parts by mass or less. Within the above ranges, the effect tends to be better obtained.
[0121] The amount of silica (parts by mass) per 100 parts by mass of the polymer component (preferably 100 parts by mass of the rubber component) / average primary particle size (nm) of the silica is preferably 0.01 or more, more preferably 0.1 or more, and even more preferably 1 or more, and is preferably 2000 or less, more preferably 1500 or less, even more preferably 1000 or less, particularly preferably 100 or less, most preferably 10 or less, and most preferably 5 or less. Within the above ranges, the effect tends to be better obtained. In this specification, the average primary particle size of silica can be determined by observing with a transmission or scanning electron microscope, measuring 400 or more primary particles of silica observed within a field of view, and averaging the measurements.
[0122] When silica is blended into the composition, it is preferable that the composition contains a silane coupling agent together with the silica. The silane coupling agent is not particularly limited, and examples thereof include bis(3-triethoxysilylpropyl)tetrasulfide, bis(2-triethoxysilylethyl)tetrasulfide, bis(4-triethoxysilylbutyl)tetrasulfide, bis(3-trimethoxysilylpropyl)tetrasulfide, bis(2-trimethoxysilylethyl)tetrasulfide, bis(2-triethoxysilylethyl)trisulfide, bis(4-trimethoxysilylbutyl)trisulfide, bis(3-triethoxysilylpropyl)disulfide, bis(2-triethoxysilylethyl)disulfide, bis(4-triethoxysilylbutyl)disulfide, bis(3-trimethoxysilylpropyl)disulfide, bis(2-trimethoxysilylethyl)disulfide, bis(4-trimethoxysilylbutyl)disulfide, 3-trimethoxysilylpropyl-N,N-dimethylthiocarbamate, Examples of the silyl silane include sulfide-based silanes such as bamoyl tetrasulfide, 2-triethoxysilylethyl-N,N-dimethylthiocarbamoyl tetrasulfide, and 3-triethoxysilylpropyl methacrylate monosulfide; mercapto-based silanes such as 3-mercaptopropyl trimethoxysilane, 2-mercaptoethyl triethoxysilane, and NXT and NXT-Z manufactured by Momentive; vinyl-based silanes such as vinyl triethoxysilane and vinyl trimethoxysilane; amino-based silanes such as 3-aminopropyl triethoxysilane and 3-aminopropyl trimethoxysilane; glycidoxy-based silanes such as γ-glycidoxypropyl triethoxysilane and γ-glycidoxypropyl trimethoxysilane; nitro-based silanes such as 3-nitropropyl trimethoxysilane and 3-nitropropyl triethoxysilane; and chloro-based silanes such as 3-chloropropyl trimethoxysilane and 3-chloropropyl triethoxysilane. These may be used alone or in combination of two or more.
[0123] As the silane coupling agent, for example, products available from Degussa, Momentive, Shin-Etsu Silicones, Tokyo Chemical Industry, Azumax, Dow Corning Toray, etc. can be used.
[0124] When containing silane coupling agent, the content of silane coupling agent is preferably 0.1 parts by mass or more, more preferably 2 parts by mass or more, and even more preferably 3 parts by mass or more, based on 100 parts by mass of silica.In addition, the content is preferably 20 parts by mass or less, more preferably 16 parts by mass or less, and even more preferably 12 parts by mass or less.When it is within the above range, the effect tends to be better obtained.
[0125] The composition preferably contains carbon black.
[0126] Examples of carbon black include N134, N110, N220, N234, N219, N339, N330, N326, N351, N550, and N762. These may be used alone or in combination of two or more kinds.
[0127] The nitrogen adsorption specific surface area of carbon black (N 2 SA) is preferably 5m 2 / g or more, more preferably 30m 2 / g or more, more preferably 60m 2 / g or more, particularly preferably 90m 2 / g or more, most preferably 120m 2 / g or more. 2 SA is preferably 300m 2 / g or less, more preferably 200m 2 / g or less, more preferably 170m 2 Within the above range, there is a tendency for the effect to be better obtained. The nitrogen adsorption specific surface area of carbon black can be determined in accordance with JIS K6217-2:2001.
[0128] The dibutyl phthalate oil absorption (DBP) of carbon black is preferably 5 ml / 100 g or more, more preferably 70 ml / 100 g or more, and even more preferably 90 ml / 100 g or more. The DBP is preferably 300 ml / 100 g or less, more preferably 200 ml / 100 g or less, even more preferably 160 ml / 100 g or less, and particularly preferably 130 ml / 100 g or less. Within the above range, the effect tends to be better. The DBP of carbon black can be measured in accordance with JIS-K6217-4:2001.
[0129] As carbon black, for example, products manufactured by Asahi Carbon Co., Ltd., Cabot Japan Co., Ltd., Tokai Carbon Co., Ltd., Mitsubishi Chemical Corporation, Lion Corporation, Shinnikka Carbon Co., Ltd., Columbia Carbon Company, etc. can be used.
[0130] The amount of carbon black per 100 parts by mass of the polymer component (preferably 100 parts by mass of the rubber component) is preferably 0.1 parts by mass or more, more preferably 1 part by mass or more, even more preferably 3 parts by mass or more, particularly preferably 5 parts by mass or more, and is preferably 200 parts by mass or less, more preferably 150 parts by mass or less, even more preferably 120 parts by mass or less, particularly preferably 80 parts by mass or less. Within the above ranges, the effect tends to be better obtained.
[0131] The amount of carbon black (parts by mass) per 100 parts by mass of the polymer component (preferably 100 parts by mass of the rubber component) / average primary particle size (nm) of carbon black is preferably 0.01 or more, more preferably 0.1 or more, and even more preferably 1 or more, and is preferably 2000 or less, more preferably 1500 or less, even more preferably 1000 or less, particularly preferably 10 or less, and most preferably 2 or less. Within the above ranges, the effect tends to be better obtained. In this specification, the average primary particle size of carbon black can be determined by observing with a transmission or scanning electron microscope, measuring 400 or more primary particles of carbon black observed within a field of view, and averaging the measurements.
[0132] The composition preferably contains sulfur. Examples of sulfur include powdered sulfur, precipitated sulfur, colloidal sulfur, insoluble sulfur, highly dispersible sulfur, soluble sulfur, etc., which are commonly used in the rubber industry. These may be used alone or in combination of two or more kinds.
[0133] As sulfur, for example, products from Tsurumi Chemical Industry Co., Ltd., Karuizawa Sulfur Co., Ltd., Shikoku Chemical Industry Co., Ltd., Flexis Corporation, Nippon Kanritsu Kogyo Co., Ltd., Hosoi Chemical Industry Co., Ltd., etc. can be used.
[0134] The sulfur content is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more, per 100 parts by mass of the polymer component (preferably 100 parts by mass of the rubber component). The content is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, even more preferably 8 parts by mass or less, and particularly preferably 5 parts by mass or less. Within the above range, the effect tends to be better obtained.
[0135] The composition preferably contains a vulcanization accelerator. Examples of the vulcanization accelerator include thiazole-based vulcanization accelerators such as 2-mercaptobenzothiazole and di-2-benzothiazolyl disulfide; thiuram-based vulcanization accelerators such as tetramethylthiuram disulfide (TMTD), tetrabenzylthiuram disulfide (TBzTD), and tetrakis(2-ethylhexyl)thiuram disulfide (TOT-N); sulfenamide-based vulcanization accelerators such as N-cyclohexyl-2-benzothiazolylsulfenamide, Nt-butyl-2-benzothiazolylsulfenamide, N-oxyethylene-2-benzothiazolesulfenamide, and N,N'-diisopropyl-2-benzothiazolesulfenamide; and guanidine-based vulcanization accelerators such as diphenylguanidine, di-orthotolylguanidine, and orthotolylbiguanidine. These may be used alone or in combination of two or more.
[0136] As the vulcanization accelerator, for example, products manufactured by Kawaguchi Chemical Co., Ltd., Ouchi Shinko Chemical Co., Ltd., Rhein Chemie AG, etc. can be used.
[0137] The content of the vulcanization accelerator is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more, based on 100 parts by mass of the polymer component (preferably 100 parts by mass of the rubber component). The content is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, even more preferably 8 parts by mass or less, and particularly preferably 5 parts by mass or less. Within the above range, the effect tends to be better obtained.
[0138] Preferably, the composition includes stearic acid. As the stearic acid, any known stearic acid can be used, for example, products available from NOF Corp., Kao Corp., Fujifilm Wako Pure Chemical Industries, Ltd., Chiba Fatty Acid Co., Ltd., and the like.
[0139] The content of stearic acid is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more, based on 100 parts by mass of the polymer component (preferably 100 parts by mass of the rubber component). The content is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, even more preferably 8 parts by mass or less, and particularly preferably 5 parts by mass or less. Within the above range, the effect tends to be better obtained.
[0140] The composition may contain zinc oxide. As the zinc oxide, any known zinc oxide can be used, for example, products available from Mitsui Mining & Smelting Co., Ltd., Toho Zinc Co., Ltd., Hakusui Tech Co., Ltd., Seido Chemical Industry Co., Ltd., Sakai Chemical Industry Co., Ltd., and the like.
[0141] The content of zinc oxide is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more, based on 100 parts by mass of the polymer component (preferably 100 parts by mass of the rubber component). The content is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, even more preferably 8 parts by mass or less, and particularly preferably 5 parts by mass or less. Within the above range, the effect tends to be better obtained.
[0142] The composition may include an anti-aging agent. Examples of the antioxidant include naphthylamine-based antioxidants such as phenyl-α-naphthylamine; diphenylamine-based antioxidants such as octylated diphenylamine and 4,4'-bis(α,α'-dimethylbenzyl)diphenylamine; N-isopropyl-N'-phenyl-p-phenylenediamine, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, and N,N'-di-2-naphthyl-p-phenylenediamine. Examples of the antioxidant include p-phenylenediamine antioxidants such as quinolinone; quinoline antioxidants such as polymers of 2,2,4-trimethyl-1,2-dihydroquinoline; monophenol antioxidants such as 2,6-di-t-butyl-4-methylphenol and styrenated phenol; and bis, tris, and polyphenol antioxidants such as tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane. These antioxidants may be used alone or in combination of two or more. Among them, p-phenylenediamine antioxidants and quinoline antioxidants are preferred, and p-phenylenediamine antioxidants are more preferred.
[0143] As the antioxidant, for example, products available from Seiko Chemical Co., Ltd., Sumitomo Chemical Co., Ltd., Ouchi Shinko Chemical Industry Co., Ltd., Flexis, etc. can be used.
[0144] The content of the antioxidant is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more, based on 100 parts by mass of the polymer component (preferably 100 parts by mass of the rubber component). The content is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, even more preferably 8 parts by mass or less, and particularly preferably 5 parts by mass or less. Within the above range, the effect tends to be better obtained.
[0145] The composition may include a wax. The wax is not particularly limited, and examples thereof include petroleum waxes such as paraffin wax and microcrystalline wax, natural waxes such as vegetable wax and animal wax, synthetic waxes such as polymers of ethylene, propylene, etc. These may be used alone or in combination of two or more kinds.
[0146] As the wax, for example, products available from Ouchi Shinko Chemical Industry Co., Ltd., Nippon Seiro Co., Ltd., Seiko Chemical Co., Ltd., etc. can be used.
[0147] The wax content is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more, based on 100 parts by mass of the polymer component (preferably 100 parts by mass of the rubber component). The content is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, even more preferably 8 parts by mass or less, and particularly preferably 5 parts by mass or less. Within the above range, the effect tends to be better obtained.
[0148] In addition to the above components, the composition may contain additives commonly used in the tire industry, such as vulcanizing agents other than sulfur (e.g., organic crosslinking agents, organic peroxides), calcium carbonate, mica such as sericite, aluminum hydroxide, magnesium oxide, clay, talc, alumina, titanium oxide, etc. The content of each of these components is preferably 0.1 parts by mass or more and preferably 200 parts by mass or less per 100 parts by mass of the polymer component (preferably the rubber component).
[0149] The composition can be produced, for example, by kneading the components using a rubber kneading device such as an open roll or a Banbury mixer, followed by vulcanization.
[0150] As for the kneading conditions, in the base kneading step in which additives other than the crosslinking agent (vulcanizing agent) and the vulcanization accelerator are kneaded, the kneading temperature is usually 100 to 180°C, preferably 120 to 170°C. In the finish kneading step in which the vulcanizing agent and the vulcanization accelerator are kneaded, the kneading temperature is usually 120°C or lower, preferably 80 to 110°C. Furthermore, the composition kneaded with the vulcanizing agent and the vulcanization accelerator is usually subjected to a vulcanization treatment such as press vulcanization. The vulcanization temperature is usually 140 to 190°C, preferably 150 to 185°C.
[0151] The composition can be used for tire components (as a rubber composition for tires) such as treads (cap treads), sidewalls, base treads, under treads, clinches, bead apex, breaker cushion rubber, carcass cord covering rubber, insulation, chafers, inner liners, and side reinforcing layers of run-flat tires. Among them, it is preferably used for treads. When used for treads, it is possible to use only the cap or only the base, but it is preferable to use both.
[0152] The tire of the present invention is manufactured by a conventional method using the above composition. That is, the composition, which contains various additives as necessary, is extruded in an unvulcanized state to match the shape of each tire component (particularly, the tread (cap tread)), molded in a conventional method on a tire building machine, laminated together with other tire components to form an unvulcanized tire, and then heated and pressurized in a vulcanizer to manufacture the tire.
[0153] The tire is not particularly limited, and examples thereof include pneumatic tires, solid tires, airless tires, etc. Among these, pneumatic tires are preferred.
[0154] The above tires are suitably used as passenger car tires, large passenger car tires, large SUV tires, truck and bus tires, motorcycle tires, racing tires, winter tires (studless tires, snow tires, studded tires), all-season tires, run-flat tires, aircraft tires, mining tires, etc. EXAMPLES
[0155] The present invention will be specifically described based on examples, but the present invention is not limited to these examples.
[0156] The various chemicals used during synthesis and polymerization were purified according to standard methods as necessary.
[0157] The methods for evaluating the obtained polymers will be described below.
[0158] (Measurement of weight average molecular weight (Mw) and number average molecular weight (Mn)) The weight average molecular weight (Mw) and number average molecular weight (Mn) of the polymer were determined by standard polystyrene conversion based on the measured values obtained by gel permeation chromatography (GPC) (GPC-8000 series, manufactured by Tosoh Corporation, detector: differential refractometer, column: TSKGEL SUPERMULTIPORE HZ-M, manufactured by Tosoh Corporation).
[0159] (Polymer structure identification) The structure of the polymer was identified by measurement using a JNM-ECA series NMR device manufactured by JEOL Ltd. The cis content was measured by infrared absorption spectroscopy.
[0160] (Polymerization of Resin A (α-methylstyrene resin (PAMS))) 1g of aluminum chloride and 200g of toluene were added to a glass flask purged with an inert gas, and 20g of α-methylstyrene (AMS monomer) was added dropwise while maintaining the internal temperature at -50 to -20°C. The reaction solution was sampled and analyzed by GPC, and the weight average molecular weight Mw was 2132, the number average molecular weight Mn was 1132, and the molecular weight distribution was 1.9. The reaction solution was then stirred at room temperature, and when the internal temperature reached 0°C or higher, 60g of water was added to the reaction solution to stop the reaction. After removing the water layer by separation, the addition of water and separation were repeated until the pH of the water layer reached 4 or higher, and the organic layer obtained by separation was dried with air to volatilize the toluene, and then dried under reduced pressure at 80°C / <10 Pa or less until a constant weight was obtained, thereby obtaining resin A. The yield was almost 100%, and the GPC analysis showed that the weight average molecular weight Mw was 2045, the number average molecular weight Mn was 980, and the molecular weight distribution was 2.1.
[0161] (Polymerization of Resin B (Ethyl Vinyl Ether Resin (Poly(ethyl vinyl ether), PEVE))) 1g of aluminum chloride and 200g of toluene were added to a glass flask purged with an inert gas, and an ethyl vinyl ether / toluene solution (20.3g of ethyl vinyl ether (EVE monomer), 100g of toluene) was added dropwise while maintaining the internal temperature at -20℃ to -5℃. The reaction solution was sampled and analyzed by GPC, and the weight average molecular weight Mw was 2201, the number average molecular weight Mn was 1202, and the molecular weight distribution was 1.8. The reaction solution was stirred at room temperature, and when the internal temperature reached 0℃ or higher, 60g of water was added to the reaction solution to stop the reaction. After removing the water layer by separation, the addition of water and separation were repeated until the pH of the water layer reached 4 or higher, and the organic layer obtained by separation was dried with air to volatilize the toluene, and then dried under reduced pressure at 80℃ / <10 Pa or less until a constant weight was obtained, to obtain resin B. The yield was almost 100%, and the GPC analysis showed that the weight average molecular weight Mw was 2205, the number average molecular weight Mn was 1110, and the molecular weight distribution was 2.0.
[0162] (Polymerization of Resin C (Poly(N-tert-butylacrylamide) (PNTBAM))) 23.9g of N-tert-butylacrylamide (NTBAM monomer) was added to a nitrogen-substituted glass flask, 200mL of toluene was added, and the mixture was stirred at room temperature for 30 minutes to obtain a uniform solution. After that, 1.10g of 2,2'-azobis(isobutyronitrile) (AIBN) was added, and the mixture was refluxed for 3 hours to react. After that, the toluene was removed using a rotary evaporator, and the mixture was dried under reduced pressure at 80℃ / 10 Pa or less until a constant weight was obtained, to obtain Resin C. The yield was nearly 100%, and GPC analysis showed that the weight average molecular weight Mw was 9721, the number average molecular weight Mn was 3736, and the molecular weight distribution was 2.6.
[0163] (Polymerization of Resin D (Poly(Nn-butylacrylamide) (PNNBAM))) 23.9 g of Nn-butylacrylamide (NNBAM monomer) was added to a nitrogen-substituted glass flask, 200 mL of toluene was added, and the mixture was stirred at room temperature for 30 minutes to obtain a uniform solution. Then, 1.10 g of 2,2'-azobis(isobutyronitrile) (AIBN) was added, and the mixture was refluxed for 3 hours to cause a reaction. After that, the toluene was removed using a rotary evaporator, and the mixture was dried under reduced pressure at 80°C / 10 Pa or less until a constant weight was reached, to obtain Resin D. The yield was nearly 100%, and GPC analysis revealed that the weight average molecular weight Mw was 9521, the number average molecular weight Mn was 3661, and the molecular weight distribution was 2.6.
[0164] (Confirmation of temperature-dependent changes in interaction with antifreeze) Each monomer or resin was added to an antifreeze solution (a liquid consisting of methanol and water, obtained by adding 9 times the volume of methanol to water and mixing at 25°C for 30 minutes) so that the concentration was 1% by mass, and the solution was gradually heated from -20°C to +20°C, and after storing at each temperature for 2 hours, it was observed whether it was clear or cloudy. The results are shown in Table 1.
[0165] [Table 1]
[0166] From Table 1, the following became clear: Each monomer was dissolved in the antifreeze at all temperatures to give a clear solution. Resin A did not dissolve in the antifreeze at any temperature. Resin B was a clear solution below 10°C, but became gradually cloudy and turned into a dispersion containing insoluble matter above 10°C. Therefore, it was found that Resin B (PEVE) has an LCST within the range of -10°C to +10°C. Resin C was a clear solution below 10°C, but became gradually cloudy and turned into a dispersion containing insoluble matter above 10°C. Therefore, it was found that Resin C (PNTBAM) has an LCST in the range of -10°C to 10°C. Resin D was a clear solution below 10°C, but became gradually cloudy and turned into a dispersion containing insoluble matter above 10°C. Therefore, it was found that Resin D (PNNBAM) has an LCST in the range of -10°C to 10°C. From the above, it has been found that a group whose interaction with the antifreeze changes with temperature (preferably a group exhibiting a lower critical solution temperature in the antifreeze, more preferably a poly(alkyl vinyl ether), a group represented by the above formula (II), even more preferably a group represented by the above formula (I) or a group represented by the above formula (II)) changes its interaction with the antifreeze with temperature change, that is, its hydrophilicity changes with temperature change, thereby changing its compatibility with other components in the composition, and thereby enabling tire performance to change in response to temperature change. Furthermore, since the lower critical solution temperature of the group is −20° C. to 20° C., the tire performance can be changed in the temperature range required for tires. Specifically, it was found that the tire performance can be changed with the temperature range as a boundary by functioning as a hydrophobic plasticizer at a temperature higher than the lower critical solution temperature of the group and functioning as a hydrophilic plasticizer at a temperature lower than the lower critical solution temperature of the group, and thus the tire performance can be changed in the temperature range required for tires.
[0167] <Synthesis of plasticizers having groups whose interactions with antifreeze change with temperature> (Polymerization of specific plasticizer A (α-methylstyrene-ethyl vinyl ether resin (PAMS-PEVE (resin B)))) 1g of aluminum chloride and 200g of toluene were added to a glass flask purged with an inert gas, and 20g of α-methylstyrene was added dropwise while maintaining the internal temperature at -50 to -20°C. The reaction solution was sampled and analyzed by GPC, and the weight average molecular weight Mw was 2165, the number average molecular weight Mn was 1202, and the molecular weight distribution was 1.8. Then, while maintaining the internal temperature of the reaction solution at -20°C to -5°C, an ethyl vinyl ether / toluene solution (20.3g of ethyl vinyl ether monomer, 100g of toluene) was added dropwise. The reaction solution was sampled and analyzed by GPC, and the weight average molecular weight Mw was 4231, the number average molecular weight Mn was 2202, and the molecular weight distribution was 1.9. The reaction solution was stirred at room temperature, and when the internal temperature reached 0°C or higher, 60g of water was added to the reaction solution to stop the reaction. After removing the aqueous layer by separation, the addition of water and separation were repeated until the pH of the aqueous layer reached 4 or more, and the organic layer obtained by separation was dried with air to volatilize the toluene, and then dried under reduced pressure at 80°C / <10 Pa or less until a constant weight was reached, to obtain specific plasticizer A. The yield was nearly 100%, and GPC analysis showed that the weight average molecular weight Mw was 4231, the number average molecular weight Mn was 2202, and the molecular weight distribution was 1.9.
[0168] (Polymerization of specific plasticizer B (α-methylstyrene-N-tert-butylacrylamide resin (PAMS-PNTBAM (resin C))) 20g of α-methylstyrene was added to a nitrogen-substituted glass flask, 25mL of toluene was added, and the mixture was stirred at room temperature for 30 minutes to obtain a uniform solution. Then, 1.10g of 2,2'-azobis(isobutyronitrile) (AIBN) was added, and the mixture was refluxed for 3 hours to cause a reaction. The reaction solution was cooled to 40°C, and 20g of N-tert-butylacrylamide was added, and the mixture was refluxed for 3 hours to cause a reaction. The reaction solution was then used to remove the toluene solvent using a rotary evaporator. The remaining dried product was dried under reduced pressure at a vacuum of 0.1 Pa or less and 80°C for 8 hours to obtain a specific plasticizer B. The yield was nearly 100%, and GPC analysis revealed that the weight average molecular weight Mw was 3265, the number average molecular weight Mn was 1256, and the molecular weight distribution was 2.6.
[0169] (Polymerization of specific plasticizer C (α-methylstyrene-Nn-butylacrylamide resin (PAMS-PNNBAM (resin D))) 20g of α-methylstyrene was added to a nitrogen-substituted glass flask, 25mL of toluene was added, and the mixture was stirred at room temperature for 30 minutes to obtain a uniform solution. Then, 1.10g of 2,2'-azobis(isobutyronitrile) (AIBN) was added, and the mixture was refluxed for 3 hours to react. The reaction solution was cooled to 40°C, and 20g of Nn-butylacrylamide was added, and the mixture was refluxed for 3 hours to react. The reaction solution was then used to remove the toluene solvent using a rotary evaporator. The remaining dried product was dried under reduced pressure at a vacuum of 0.1 Pa or less and 80°C for 8 hours to obtain a specific plasticizer C. The yield was nearly 100%, and GPC analysis revealed that the weight average molecular weight Mw was 3374, the number average molecular weight Mn was 1123, and the molecular weight distribution was 3.0.
[0170] (Polymerization of specific plasticizer D (α-methylstyrene-ethyl vinyl ether resin (oil-type PAMS-PEVE (resin B))) 1g of aluminum chloride and 200g of toluene were added to a glass flask purged with an inert gas, and 5g of α-methylstyrene was added dropwise while maintaining the internal temperature at -50 to -20°C. The reaction solution was sampled and analyzed by GPC, and the results were weight average molecular weight Mw; 980, number average molecular weight Mn; 602, and molecular weight distribution 1.6. Thereafter, an ethyl vinyl ether / toluene solution (35.0g of ethyl vinyl ether monomer, 100g of toluene) was added dropwise while maintaining the internal temperature at -20°C to -5°C. The reaction solution was sampled and analyzed by GPC, and the results were weight average molecular weight Mw; 1127, number average molecular weight Mn; 701, and molecular weight distribution 1.6. The reaction solution was stirred at room temperature, and when the internal temperature reached 0°C or higher, 60g of water was added to the reaction solution to stop the reaction. After removing the aqueous layer by separation, the addition of water and separation were repeated until the pH of the aqueous layer reached 4 or more, and the organic layer obtained by separation was then dried with air to volatilize the toluene, and then dried under reduced pressure at 80°C / <10 Pa or less until a constant weight was reached, to obtain specific plasticizer D. The yield was nearly 100%, and GPC analysis showed that the weight average molecular weight Mw was 1042, the number average molecular weight Mn was 604, and the molecular weight distribution was 1.7.
[0171] (Polymerization of specific plasticizer E (liquid resin (polybutadiene) -PEVE (resin B))) 1g of aluminum chloride and 200g of toluene were added to a glass flask purged with an inert gas, and while maintaining the internal temperature at -50 to -20°C, ethyl vinyl ether / toluene solution (20.0g of ethyl vinyl ether monomer, 100g of toluene) was added dropwise. The reaction solution was sampled and analyzed by GPC, and the weight average molecular weight Mw was 1129, the number average molecular weight Mn was 988, and the molecular weight distribution was 1.6. Thereafter, while maintaining the internal temperature of the reaction solution at -20°C to -5°C, maleic acid-modified BR / toluene solution (20.0g of maleic acid-modified liquid BR Ricon 130MA8, 100g of toluene) was added dropwise. The reaction solution was sampled and analyzed by GPC, and after confirming the appearance of a new peak on the polymer side from the raw maleic acid-modified BR, the reaction solution was stirred at room temperature, and when the internal temperature reached 0°C or higher, 60g of water was added to the reaction solution to stop the reaction. After removing the aqueous layer by separation, the addition of water and separation were repeated until the pH of the aqueous layer reached 4 or more, and the organic layer obtained by separation was dried with air to volatilize the toluene, and then dried under reduced pressure at 80°C / <10 Pa or less until a constant weight was reached, to obtain specific plasticizer E. The yield was nearly 100%, and GPC analysis showed that the weight average molecular weight Mw was 3631, the number average molecular weight Mn was 2804, and the molecular weight distribution was 1.3.
[0172] (Specific plasticizer F (Polymerization of polystyrene-ethyl vinyl ether resin (PS-PEVE (resin B))) 1g of aluminum chloride and 200g of toluene were added to a glass flask purged with an inert gas, and 20g of styrene was added dropwise while maintaining the internal temperature at 0 to 20°C. The reaction liquid was sampled and analyzed by GPC, and the weight average molecular weight Mw was 1565, the number average molecular weight Mn was 1122, and the molecular weight distribution was 1.4. Thereafter, an ethyl vinyl ether / toluene solution (20.3g of ethyl vinyl ether monomer, 100g of toluene) was added dropwise while maintaining the internal temperature at 0 to 20°C. The reaction liquid was sampled and analyzed by GPC, and the weight average molecular weight Mw was 3231, the number average molecular weight Mn was 2302, and the molecular weight distribution was 1.4. The reaction liquid was stirred at room temperature, and when the internal temperature reached 20°C or higher, 60g of water was added to the reaction liquid to stop the reaction. After removing the aqueous layer by separation, the addition of water and separation were repeated until the pH of the aqueous layer reached 4 or more, and the organic layer obtained by separation was dried with air to volatilize the toluene, and then dried under reduced pressure at 80°C / <10 Pa or less until a constant weight was reached, to obtain specific plasticizer F. The yield was nearly 100%, and GPC analysis showed that the weight average molecular weight Mw was 3331, the number average molecular weight Mn was 2342, and the molecular weight distribution was 1.4.
[0173] (Polymerization of specific plasticizer G (polyterpene-ethyl vinyl ether resin (PTR-PEVE (resin B))) 1g of aluminum chloride and 200g of toluene were added to a glass flask purged with an inert gas, and 20g of β-pinene was added dropwise while maintaining the internal temperature at 0 to 20°C. The reaction solution was sampled and analyzed by GPC, and the weight average molecular weight Mw was 1065, the number average molecular weight Mn was 802, and the molecular weight distribution was 1.3. Thereafter, an ethyl vinyl ether / toluene solution (20.3g of ethyl vinyl ether monomer, 100g of toluene) was added dropwise while maintaining the internal temperature at 0 to 20°C. The reaction solution was sampled and analyzed by GPC, and the weight average molecular weight Mw was 2252, the number average molecular weight Mn was 1165, and the molecular weight distribution was 1.9. The reaction solution was stirred at room temperature, and when the internal temperature reached 20°C or higher, 60g of water was added to the reaction solution to stop the reaction. After removing the aqueous layer by separation, the addition of water and separation were repeated until the pH of the aqueous layer reached 4 or more, and the organic layer obtained by separation was dried with air to volatilize the toluene, and then dried under reduced pressure at 80°C / <10 Pa or less until a constant weight was reached, to obtain specific plasticizer G. The yield was nearly 100%, and GPC analysis showed that the weight average molecular weight Mw was 2382, the number average molecular weight Mn was 1342, and the molecular weight distribution was 1.8.
[0174] The specific plasticizers A to G produced as described above are plasticizers having a group whose interaction with the antifreeze solution changes depending on the temperature, and the lower critical solution temperature of the group is -20°C to 20°C.
[0175] <Synthesis of polymer (rubber component)> (Polymerization of Polymer A) In a heat-resistant container that had been thoroughly substituted with nitrogen, 1500 ml of n-hexane, 25 g of styrene, 75 g of 1,3-butadiene, 0.2 mmol of tetramethylethylenediamine, and 0.24 mmol of n-butyllithium were added and stirred at 0°C for 48 hours. After that, alcohol was added to stop the reaction, and 24 mL of a 1 mmol / L BHT ethanol solution was added to the reaction solution. 10 mL of the polymerization solution was collected, precipitated with 40 mL of ethanol, and dried to obtain polymer A. The obtained copolymer had a weight average molecular weight of 460,000, a styrene content of 25 mass%, and a yield of 99%.
[0176] (Polymerization of Polymer B) Preparation of catalyst solution B 350 mL of cyclohexane, 35 g of 1,3-butadiene monomer, 54 mL of 20 vol% neodymium versatate / cyclohexane solution, and 130 mL of PMAO / toluene solution were added and stirred for 30 minutes, then 30 mL of 1 M DAIBAH / hexane solution was added and stirred for 30 minutes, and then 15 mL of 1 M 2-chloro-2-methylpropane / cyclohexane solution was added and stirred for 30 minutes to prepare catalyst solution B. Polymerization of Polymer B In a dried and nitrogen-purged 3L pressure-resistant stainless steel vessel, 2000mL of cyclohexane and 100g of 1,3-butadiene were added, 10mL of 1mol / L TIBA / normal hexane solution was added, and the mixture was stirred for 5 minutes. After confirming that the solution was clear, 30mL of catalyst solution B was added and the polymerization reaction was carried out at 80°C for 3 hours. After 3 hours, 50mL of 1M isopropanol / THF solution was dropped as a reaction terminator to terminate the reaction. 10mL of the polymerization solution was collected, precipitated with 40mL of ethanol, and dried to obtain polymer B. The obtained polymer had a weight average molecular weight of 800,000, a cis content of 98% by mass, and a yield of 99%.
[0177] (Production of hydrogenated SBR) n-Hexane, styrene, 1,3-butadiene, TMEDA (N,N,N',N'-tetramethylethylenediamine), and n-butyllithium were added to a heat-resistant reaction vessel that had been thoroughly substituted with nitrogen, and the mixture was stirred at 50°C for 5 hours to carry out a polymerization reaction. After that, the mixture was stirred for 20 minutes while supplying hydrogen gas at a pressure of 0.4 MPa-Gauge, and reacted with the unreacted lithium at the polymer end to produce lithium hydride. The hydrogen gas supply pressure was set to 0.7 MPa-Gauge, the reaction temperature was set to 90°C, and hydrogenation was carried out using a catalyst mainly composed of titanocene dichloride. When the absorption of hydrogen reached the cumulative amount that would result in the desired hydrogenation rate, the reaction temperature was set to room temperature, the hydrogen pressure was returned to normal pressure, and the mixture was removed from the reaction vessel, the reaction solution was stirred and poured into water, and the solvent was removed by steam stripping to obtain hydrogenated SBR.
[0178] Various chemicals used in the following Examples and Comparative Examples will be collectively described below. NR: TSR20 (natural rubber) SBR: Polymer A Hydrogenated SBR: The above hydrogenated SBR (conjugated diene units: 3.3 mol%, non-conjugated olefin units: 88.2 mol%, aromatic vinyl units: 8.5 mol% (styrene amount: 25 mass%), Mw: 450,000) BR: Polymer B Resins A to D: Resins A to D Specific plasticizers A to G: Specific plasticizers A to G listed above Carbon black: N110 (N) manufactured by Cabot Japan Co., Ltd. 2 SA:144m 2 / g, DBP: 115ml / 100g, average primary particle size: 18nm) Silica: Ultrasil VN3 (N) manufactured by Evonik Tegussa 2 SA: 175m 2 / g, average primary particle diameter: 16nm) Silane coupling agent: Si69 (bis(3-triethoxysilylpropyl)tetrasulfide) manufactured by Evonik Tegussa Anti-aging agent: Nocrac 6C (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Stearic acid: stearic acid manufactured by NOF Corporation Zinc oxide: Zinc oxide No. 1 manufactured by Mitsui Mining & Smelting Co., Ltd. Sulfur: Powdered sulfur manufactured by Tsurumi Chemical Co., Ltd. Vulcanization accelerator (1): Noccela CZ (N-cyclohexyl-2-benzothiazolyl sulfenamide) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Vulcanization accelerator (2): Noccelaer D (1,3-diphenylguanidine) manufactured by Ouchi Shinko Chemical Industry Co., Ltd.
[0179] Examples and Comparative Examples According to the compounding recipe shown in Table 2, chemicals other than sulfur and vulcanization accelerator were kneaded for 5 minutes at 150°C using a 1.77L Banbury mixer manufactured by Kobe Steel, Ltd. to obtain a kneaded product. Next, sulfur and vulcanization accelerator were added to the kneaded product obtained, and the mixture was kneaded for 5 minutes at 80°C using an open roll to obtain an unvulcanized rubber composition. The resulting unvulcanized rubber composition was press-vulcanized at 170° C. for 15 minutes to obtain a vulcanized rubber composition.
[0180] The vulcanized rubber compositions thus obtained were subjected to the following evaluations, and the results are shown in Table 2.
[0181] (low fuel consumption) The tan δ of the vulcanized rubber composition was measured at a dynamic strain amplitude of 1%, a frequency of 10 Hz, and a temperature of 50° C. using a spectrometer manufactured by Ueshima Seisakusho Co., Ltd. The reciprocal value of tan δ was expressed as an index, with the value of Comparative Example 1 being set at 100. A larger value indicates a smaller rolling resistance and better fuel economy.
[0182] (Wet grip performance) The wet grip performance was evaluated using a flat belt type friction tester (FR5010 type) manufactured by Ueshima Seisakusho Co., Ltd. Using a cylindrical rubber test piece (width 20 mm, diameter 100 mm) made of the above vulcanized rubber composition, the following conditions were used: speed 20 km / hour, load 4 kgf, road surface temperature 20°C. The slip of the sample against the road surface was changed from 0 to 70%, and the maximum friction coefficient detected at that time was read and expressed as an index with Comparative Example 1 being set at 100. A larger value indicates a higher maximum friction coefficient and better wet grip performance.
[0183] The overall performance of fuel economy and wet grip performance is expressed as the sum of the two indices of fuel economy and wet grip performance.
[0184] [Table 2]
[0185] From Table 2, it can be seen that the compositions of the examples, which contain a plasticizer for resins and / or elastomers having a group whose interaction with antifreeze changes depending on temperature and whose lower critical solution temperature of the group is -20°C to 20°C, can change tire performance in the temperature range required for tires, and can be used to produce a tire composition.
Claims
1. The antifreeze solution has a group whose interaction with the antifreeze solution changes depending on the temperature, and the lower critical solution temperature of the group is −20° C. to 20° C.; Plasticizers for resins and / or elastomers, either oils, ester-based plasticizers, liquid or solid resins.
2. The plasticizer according to claim 1 , wherein the group is a group represented by the following formula (I) or a group represented by the following formula (II): 【Chemistry 1】 (In the formula, n represents an integer of 1 to 1000, R 1 , R 2 and R 3 each independently represents a hydrogen atom or a hydrocarbyl group. 【Chemistry 2】 (In the formula, n represents an integer of 1 to 1000, R 4 represents an n-butyl group or a tert-butyl group, R 5 represents a hydrogen atom or a hydrocarbyl group.
3. 3. The plasticizer according to claim 1 or 2, wherein the group is poly(ethyl vinyl ether), poly(N-tert-butylacrylamide), poly(N-n-butylacrylamide).
4. A composition comprising the plasticizer according to any one of claims 1 to 3.
5. The composition of claim 4 which comprises a rubber.
6. 6. The composition of claim 5, comprising as the rubber a multicomponent copolymer containing conjugated diene units, non-conjugated olefin units and aromatic vinyl units.
7. The composition according to claim 5 or 6, which contains silica, and the amount (parts by mass) of silica per 100 parts by mass of the rubber component / average primary particle size (nm) of the silica is 1 to 1,000.
8. The composition according to any one of claims 5 to 7, which contains carbon black, and the amount (parts by mass) of the carbon black per 100 parts by mass of the rubber component / average primary particle diameter (nm) of the carbon black is 1 to 1,000.
9. The composition according to any one of claims 4 to 8, which is for use in a tire tread.
10. A tire having tire components using the composition according to any one of claims 4 to 9.
11. 11. The tire of claim 10, wherein the tire component is a tread.
Citation Information
Patent Citations
Rubber composition and pneumatic tire using the same
JP2008214377A
Method of making graft copolymer
JP2013136748A
Rubber composition and pneumatic tire
JP2013136749A
Copolymer, manufacturing method thereof, rubber composition, and tire
JP2013139563A
Rubber composition for tires with good wet grip and rolling resistance properties
WO2020002439A1